An Emotional Intelligence and Religious Orientation among Volunteers and Non- Volunteers in Malaysia - Nurul Hudani Md Nawi; Puteri Hayati Megat Ahmad (Asian Social Work Journal, 2018)
An investigation into the characteristics of volunteers is important to understand why people volunteer. From an applied point of view, these understanding can help to better manage and retain the volunteers in voluntary organizations. The present study compared volunteers and non-volunteers in Sabah using a cross-sectional survey method. Questionnaire packet consisting of measures of religious orientation, and emotional intelligence were self-administered by the respondents. One hundred and sixty eight of them were volunteers and one hundred and eight were non-volunteers. Findings showed that there was no significant difference between volunteers and non-volunteers in term of emotional intelligence (t=-0.13 p>0.05). However, both aspects in religious orientation i.e. Intrinsic Religious Orientation (t=3.96, p<0.05) and Extrinsic-Personal Orientation (t=3.74, p< 0.05) showed that there were significant differences between volunteers and non-volunteers. Moreover, the result showed that volunteers have low mean score for both aspect in religious orientation namely Intrinsic Orientation (mean=19.19, SD: 2.32) and Extrinsic–Personal Orientation (mean=7.83, SD: 1.68) compared to non-volunteers (mean=20.29, SD: 2.06) and (mean=8.44, SD: 1.01). It showed that, mostly volunteers reported less personal gain from embracing religion. The results was also indicated that volunteers can be distinguished from non-volunteers in term of religious orientation. On a practical note, the assessment of EI in voluntary workers could possibly assist in enhancing the human resource management plan especially in training development. Excellent management of this unique group of workers can lead to the success of voluntary organizations in delivering huge benefits to the society.